The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Nadia Pinardi; Johan Stander; David M. Legler; Kevin O'Brien; Tim Boyer; Tom Cuff; Pierre Bahurel; Mathieu Belbeoch; Sergey Belov; Shelby Brunner; Eugene Burger; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Feather mites play a role in cleaning host feathers: New insights from DNA metabarcoding and microscopy - Jorge Doña; Heather Proctor; David Serrano; Kevin P. Johnson; Arnika Oddy‐van Oploo; Jose C. Huguet‐Tapia; Marina S. Ascunce; Roger Jovani (Molecular Ecology, 2019)
Parasites and other symbionts are crucial components of ecosystems, regulating host populations and supporting food webs. However, most symbiont systems, especially those involving commensals and mutualists, are relatively poorly understood. In this study, we have investigated the nature of the symbiotic relationship between birds and their most abundant and diverse ectosymbionts: the vane‐dwelling feather mites. For this purpose, we studied the diet of feather mites using two complementary methods. First, we used light microscopy to examine the gut contents of 1,300 individual feather mites representing 100 mite genera (18 families) from 190 bird species belonging to 72 families and 19 orders. Second, we used high‐throughput sequencing ( HTS ) and DNA metabarcoding to determine gut contents from 1,833 individual mites of 18 species inhabiting 18 bird species. Results showed fungi and potentially bacteria as the main food resources for feather mites (apart from potential bird uropygial gland oil). Diatoms and plant matter appeared as rare food resources for feather mites. Importantly, we did not find any evidence of feather mites feeding upon bird resources (e.g., blood, skin) other than potentially uropygial gland oil. In addition, we found a high prevalence of both keratinophilic and pathogenic fungal taxa in the feather mite species examined. Altogether, our results shed light on the long‐standing question of the nature of the relationship between birds and their vane‐dwelling feather mites, supporting previous evidence for a commensalistic–mutualistic role of feather mites, which are revealed as likely fungivore–microbivore–detritivore symbionts of bird feathers.

Front Cover - Jorge Doña; Heather Proctor; Sergey Mironov; David Serrano; Roger Jovani (Global Ecology and Biogeography, 2018)

Host specificity, infrequent major host switching and the diversification of highly host‐specific symbionts: The case of vane‐dwelling feather mites - Jorge Doña; Heather Proctor; Sergey Mironov; David Serrano; Roger Jovani (Global Ecology and Biogeography, 2018)
Aim Highly host‐specific symbionts are very rarely found except with their typical host species. Although switches to new hosts are rare and difficult to detect, a switch to a host phylogenetically distant from the original one (a ‘major host switch’) could allow diversification of the symbionts onto the new host lineage. The consequences of such major host switches on the diversification of highly host‐specific symbionts of animals have rarely been explored. Here, we examine the host specificity of vane‐dwelling feather mites, a group that shows strong specificity, together with their host‐switching dynamics and the consequences of major host switches for their diversification. Location Global. Time period From 1882 to 2015. Major taxa studied Feather mites and birds. Methods Using the largest published dataset of feather mite–bird associations, we analysed raw, phylogenetic and geographical host specificity of feather mites. We studied host‐switching dynamics by describing the sharing by feather mites of bird species with different phylogenetic distances. For three of the most species‐rich feather mite families, we quantified the consequences of major host switches for feather mite diversification. Results Most feather mite species (84%) inhabit one to three very closely related host species. Assemblages of feather mites on birds do not show a geographical signature, but rather show strong host‐driven structuring. The probability that a mite species occurs on two host species decays sharply with host phylogenetic distance, with only one instance of a feather mite species occupying distantly related hosts from different orders. However, results suggest that despite the strong host specificity, a few major host switches triggered the origin of 21% of the species and 38% of the genera of the mite families studied. Main conclusions We show that feather mites are highly host‐specific symbionts, whose assemblages do not show geographical structure, even at a continental scale. We conclude that major host switches are very rare events with strong macroevolutionary consequences for feather mite diversity.

Information infrastructure for Australia’s Integrated Marine Observing System - Marton G. Hidas; Roger Proctor; Natalia Atkins; Julian Atkinson; Laurent Besnard; Peter Blain; Philip Bohm; Jon Burgess; Kim Finney; Dan Fruehauf; Guillaume Galibert; Xavier Hoenner; et al. (Earth Science Informatics, 2016)

Global associations between birds and vane‐dwelling feather mites - Jorge Doña; Heather Proctor; Sergey Mironov; David Serrano; Roger Jovani (Ecology, 2016)
Understanding host–symbiont networks is a major question in evolutionary ecology. Birds host a great diversity of endo‐ and ectosymbiotic organisms, with feather mites (Arachnida: Acariformes: Analgoidea, Pterolichoidea) being among the most diverse of avian symbionts. A global approach to the ecology and evolution of bird–feather‐mite associations has been hampered because of the absence of a centralized data repository. Here we present the most extensive data set of associations between feather mites and birds. Data include 12 036 records of 1887 feather mite species located on the flight feathers of 2234 bird species from 147 countries. Feather mites typically located inside quills, on the skin, or on downy body feathers are not included. Data were extracted from 493 published sources dating from 1882 to 2015. Data exploration shows that although most continents and bird families are represented, most bird species remain unexplored for feather mites. Nevertheless, this is the most comprehensive data set available for enabling global macroecological analyses of feather mites and their hosts, such as ecological network analyses. This metadata file outlines the structure of these data and provides primary references for all records used.

Editorial to the second PECS 2008 special issue of Ocean Dynamics - Alejandro J. Souza; Roger Proctor (Ocean Dynamics, 2010)

Editorial to the first PECS 2008 special issue of Ocean Dynamics - Alejandro J. Souza; Roger Proctor (Ocean Dynamics, 2009)

APPLICATIONS IN COASTAL MODELING AND FORECASTING - Pierre De Mey; Peter Craig; Fraser Davidson; Christopher Edwards; Yoichi Ishikawa; John Kindle; Roger Proctor; Keith Thompson; Jiang Zhu (Oceanography, 2009)

Assessing the value of GODAE products in coastal and shelf seas - Pierre De Mey; Roger Proctor (Ocean Dynamics, 2009)

The influence of initial conditions and open boundary conditions on shelf circulation in a 3D ocean-shelf model of the North East Atlantic - Sarah L. Wakelin; Jason T. Holt; Roger Proctor (Ocean Dynamics, 2009)

Mesostigmatid Mites (Acari: Mesostigmata) on Rainforest Tree Trunks: Arboreal Specialists, but Substrate Generalists? - Frédéric Beaulieu; David E. Walter; Heather C. Proctor; Roger L. Kitching; Florian Menzel (Experimental and Applied Acarology, 2006)

Modelling the transport of larval sandeels on the north‐west European shelf - ROGER PROCTOR; PETER J. WRIGHT; ANDREW EVERITT (Fisheries Oceanography, 1998)
This study considers the interannual variability in the advection of sandeel ( Ammodytes marinus ) larvae on the north‐west European shelf. We use recently collated data on spawning location, age of larvae and the time of hatching (between 1955 and 1993) as input to a particle‐tracking model. Utilizing hourly currents from a 39 year run of a two‐dimensional sea circulation model, cohorts of sandeel larvae were represented as a distribution of particles in space and time, and particle drift was calculated for the larval life stage. The final distributions of particles were compared with actual distributions of 0‐group sandeels in the North Sea, as determined from surveys conducted at around the end of the larval phase. Preliminary examination of the data between 1973 and 1993 indicates that differences in predicted drift could explain some of the large interannual variability in 0‐group distributions. This approach may help to improve our understanding of the frequent colonization events that are typical of this species.

Numerical investigation into the effect of freshwater inputs on the circulation in Pelorus Sound, New Zealand - Roger Proctor; Mark Hadfield (New Zealand Journal of Marine and Freshwater Research, 1998)
Observations collected in Beatrix Bay, a small bay within Pelorus Sound, New Zealand, show that although the bay is thermally stratified for much of the year, salinity stratification as a result of intermittent rainfall and river inflow plays a dominant role in the density structure and circulation within the Bay. A 3‐dimensional baroclinic model of Pelorus Sound is developed and applied to the simulation of idealised pulses of rainfall and river inflow to investigate their impact on the density structure and circulation within Pelorus Sound, focusing on Beatrix Bay. The model shows that the rainfall causes near‐surface salinity stratification of 1–2 psu, sufficient to introduce phase differences of c. 2 h between surface and bottom M 2 tidal currents. Following the river inflow, a surface tongue of fresher water is seen to propagate towards the mouth of the Sound, taking c. 4.5 days to reach Beatrix Bay, by which time tidal stirring in the Sound has caused the fresh water to become almost well‐mixed.